ADSORPSI LOGAM BERAT KADMIUM (Cd) OLEH AMPAS KOPI LIMBAH DARI KEDAI KOPI - Lisva Christye; Teguh Wirawan; Nanang Tri Widodo (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Adsorption of Cadmium Heavy Metal (Cd) by Coffee Waste from Coffee Shops has been carried out. The purpose of this study was to determine the optimum contact time, optimum pH and maximum adsorption capacity and the type of adsorption isotherm on the adsorption of cadmium by coffee grounds. In the preparation stage, the coffee grounds were rinsed using boiling distilled water several times, then sieved using a 60 mesh sieve, the adsorption process in this study used the Batch method. Cadmium metal was analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that the optimum time was optained at 30 minutes, the optimum pH was at pH 6 and the maximum adsorption capacity was 66,74 mg/g. The type of adsorption isotherm obtained is Freundlich isoterm. Keywords: Adsorption, coffee grounds, cadmium.